Survival of Fiber-Reinforced Composite Resin Post-Restored vs. Cast Post-and-Core-Restored Teeth: A Retrospective Clinical Study - Oskar Bunz; Darja Iwantschenko; Sabrina Tulka; Claudia Barthel-Zimmer; Andree Piwowarczyk (MDPI AG, 2021)
Objective: The question of whether classic cast post-and-core (CPC) or fiber-reinforced composite resin posts (FRCP) are the best clinical decision has still not been fully solved. Materials and Methods: One hundred and sixty-two teeth were restored with FRCP, and 162 CPC restored teeth were included in this study with a matched-pair design. In a primary analysis, the survival rates after one year (primary endpoint) were compared. The additional analysis included an evaluation of tooth- and construction-specific variables and an illustration of the survival up to 60 months via Kaplan-Meier curves. Results: FRCP showed lower failure risk considering the definitive prosthetic restoration and tooth type compared to CPC restored teeth. In total, 17 failures were observed in the FRCP group and 35 failures in the CPC group. A 60-month survival rate of 79.3% for FRCP and 64.5% for CPC was observed. Teeth serving as abutments for telescopic dentures were more likely to be affected by failure compared to teeth restored with single crowns. Conclusion: Within the limitations of this study, the FRCP showed a lower failure risk compared to the CPC, considering the definitive prosthetic restoration and tooth type within the observation period.